No going back: Why we cannot restore Glass-Steagall's segregation of banking and finance - Jan Kregel (Levy Economics Institute of Bard College, 2010)
The purpose of the 1933 Banking Act-aka Glass-Steagall-was to prevent the exposure of commercial banks to the risks of investment banking and to ensure stability of the financial system. A proposed solution to the current financial crisis is to return to the basic tenets of this New Deal legislation. Senior Scholar Jan Kregel provides an in-depth account of the Act, including the premises leading up to its adoption, its influence on the design of the financial system, and the subsequent collapse of the Act's restrictions on securities trading (deregulation). He concludes that a return to the Act's simple structure and strict segregation between (regulated) commercial and (unregulated) investment banking is unwarranted in light of ongoing questions about the commercial banks' ability to compete with other financial institutions. Moreover, fundamental reform - the conflicting relationship between state and national charters and regulation - was bypassed by the Act.
Keywords: 330